Secondary School Teachers’ Attitude Towards the Use of Social Media as a Teaching Platform in Nigeria - Jabai, Faith Shekwagu (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Secondary School Teachers‘ attitude towards the use of social media as a platform for educational purposes in Nigeria. The main aim of the study is to investigate secondary school teachers‘ attitude towards use of social media as a teaching platform. The study makes use of quantitative methodology. 112 teachers within the country‘s capital city- Abuja participated as respondents to the distributed questionnaires. Findings reveal that teachers are familiar with at least two social media platforms namely Facebook and Youtube and frequent users of the aforementioned platforms as well. However, the least frequent and familiar sites are LinkedIn and Slideshare. The general attitude of the teachers are positive towards social media usage. Age and gender had no effect to teachers‘ general attitude towards social media.

ÖZ: Bu çalışmanın temel amacı, Nigerya – Abuja‘da orta öğretim okullarında görev yapmakta olan öğretmenlerinin sosyal medya ortamlarını öğretim amaçlı kullanmalarına yönelik tutumlarını incelemektedir. Çalışma nicel bir çalışma olarak düzenlenmiştir. Araştırmanın çalışma grubu Nijerya Abuja kentinde görev yapmakta olan 112 öğretmenden oluşmuştur. Çalışma sonucunda öğretmenlerin en az iki sosyal medya ortamına aşina oldukları (Facebook ve YouTube) ve en sık kullandıkları sosyal medya ortamlarının da Facebook ve YouTube olduğu tespit edilmiştir. Ayrıca çalışma sonucunda öğretmenlerin en az kullandıkları sosyal medya ortamlarının da LinkedIn ve Slideshare olduğu belirlenmiştir. Ek olarak çalışmada, öğretmenlerin sosyal medyaya yönelik olumlu tutumları olduğu ortaya çıkarılmıştır. Ancak öğretmenlerin cinsiyet ve yaşlarının sosyal medyaya yönelik tutumlarının üzerinde etkisinin olmadığı görülmüştür.
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Computer and Instructional Technology Teacher Education, 2017. Supervisor: Assoc. Prof. Dr. Ersun İşçioğlu.
Keywords: Computer and Instructional Technology Teacher Education; Information and Communication Technologies in Education; Internet in education--Educational technology--Social aspects--Social media; Education - Computer network resources--Social Media--Teaching Platform; Social Media--Educational Technology--Teacher Attitudes; Teaching - Computer network resources; Information Communication Technology (ICT); Social Media; Teachers‘ Attitude